2016
DOI: 10.13005/ojc/320529
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Acid Activation and Thermodynamic Characteristics of Aluminosilicates in Sorption Process of Phosphorus Release from Sludges

Abstract: One of the actual problems of the phosphoric industry is complex usage of all got raw materials and processing of technogenic waste with receiving products. One of the main waste of phosphoric production are the phosphorus-containing sludges which are formed on stages of condensation of vaporous phosphorus. Despite numerous researches on suppression and processing of phosphoric sludges, today the universal way of their processing meeting the requirements of phosphorus production isn't found yet. In this regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…As a literature review has shown, to obtain clay adsorbents for the purification of liquid hydrocarbons, mineral oils, paraffins and ceresins, bentonites, palygorskites, opoka-like and hydromica clays, which are available in sufficient quantities in Uzbekistan, are widely used [5,6,7,8].…”
Section: Methodsmentioning
confidence: 99%
“…As a literature review has shown, to obtain clay adsorbents for the purification of liquid hydrocarbons, mineral oils, paraffins and ceresins, bentonites, palygorskites, opoka-like and hydromica clays, which are available in sufficient quantities in Uzbekistan, are widely used [5,6,7,8].…”
Section: Methodsmentioning
confidence: 99%
“…При этом ион, заряженный положительно, адсорбируется преимущественно на сорбентах с отрицательно заряженной поверхностью, и наоборот. Эти процессы обычно сопровождаются явлением обмена ионами между адсорбентом и раствором -так называемой ионообменной адсорбцией [2][3][4].…”
Section: Mathematical Description Of the Process Of Sorption Treatmen...unclassified
“…The absorption regions at 350°C, 650°C, and desorption at 433°C are determined with method of thermo programmed reduction and hydrogen desorption. Thermodynamic studies of calculating 1,2 Gibbs energy of possible synthesis conversion of sorbent minerals with the addition of oil sludge have established that the greatest thermodynamic probability is characterized by the synthesis of minerals in the presence of C 6 H 6 , and the lowest is in the presence of methane.…”
Section: Introductionmentioning
confidence: 99%